Effect of varicocelectomy and/or mast cells stabilizer on sperm DNA fragmentation in infertile patients with varicocele. (1st December 2017) - Zaazaa, A.; Adel, A.; Fahmy, I.; Elkhiat, Y.; Awaad, A. A.; Mostafa, T.
Summary: This study aimed to assess the effect of varicocelectomy and/or mast cells (MCs) stabilizer on sperm DNA fragmentation in infertile men with varicocele (Vx). Overall, 120 infertile patients were randomized to three equal treatment arms; patients that underwent varicocelectomy, patients on 1 mg ketotifen twice daily for three months, and patients that underwent varicocelectomy followed with 1 mg ketotifen twice daily for three months. These patients were subjected to history taking, clinical examination, semen analysis, and estimation of sperm DNA fragmentation index (DFI). After 3 months, all investigated groups showed significant improvement regarding the mean total sperm count, sperm concentration, total sperm motility, and sperm normal forms percentage compared with the pre‐treatment data. As well, the mean sperm DFI was significantly improved compared with the pre‐treatment data; in men that underwent varicocelectomy (34.6% vs. 28.3%), in men on MC stabilizer only (33.4% vs. 27.8%), and in men that underwent varicocelectomy followed by MC stabilizer (34.3% vs. 25.1%). Sperm DFI improvement percentages showed the highest improvement in men that underwent varicocelectomy followed with MC stabilizer compared with the other two groups (26.8% vs. 18.2%, 16.8%). Sperm DFI improvement percentages showed significant increases in the infertile patients with Vx grade III compared to Vx grade II in all investigated groups. It is concluded that in infertile men associated with Vx and high sperm DFI, surgical repair followed with MCs stabilizer significantly improve sperm DFI compared with either surgical repair or MCs stabilizer alone.